Analisis Komparatif Krisis Likuiditas Sektoral pada Palestine Exchange (PEX) dan Bursa Efek Indonesia (BEI) - Hasbih Soleh Suryadi; Maryam Batubara (Economic Reviews Journal, 2026)
This study aims to comparatively analyze the impact of monetary structures and Islamic financial architecture on the stability of banking sectors listed on capital markets, using the Palestine Exchange (PEX) and the Indonesia Stock Exchange (IDX) as case studies. Employing a political-economy approach and structural analysis, the study examines how the absence of monetary sovereignty triggered the anomaly known as "The Shekel Surplus Crisis" in Palestine, contrasting it with the single, Rupiah-based monetary transmission mechanism in Indonesia. Furthermore, the study explores how Islamic financial instruments on both exchanges responded to these liquidity challenges. The analysis reveals that both conventional and Islamic banking issuers on the PEX face extreme operational risks due to the accumulation of unproductive physical capital (Shekels)—which cannot be digitized owing to repatriation quota restrictions imposed by the Central Bank of Israel—coupled with a lack of liquidity management instruments for Islamic finance in Palestine. Conversely, mandatory Rupiah regulations and the availability of Islamic money market instruments (PUAS) on the IDX—fully supported by Bank Indonesia—have proven effective in creating a stable liquidity buffer. The study concludes that capital market performance and the resilience of the Islamic finance industry are not determined solely by Shariah compliance or infrastructure modernization but are intrinsically linked to a nation's monetary sovereignty. (UNCTAD, 1994; IMF, 2022; Bank Indonesia, 2008; Bank Indonesia, 2024).